KONTROVERSI SERTIFIKASI HALAL MIXUE: TINJAUAN ETIKA BISNIS TERHADAP TANGGUNG JAWAB PERUSAHAAN ASING DI INDONESIA (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The controversy over Mixue's halal certification in Indonesia has raised concerns regarding business ethics and social responsibility of foreign companies. This research aims to analyze how Mixue deals with halal regulations and the impact of the unclear halal status of its products in the Muslim-majority market. The method used is qualitative with literature study. The results show that Mixue's lack of transparency and communication led to a crisis of consumer confidence and negative reactions from religious institutions such as MUI. Mixue was perceived as ignoring social responsibility by opening massive outlets without a clear official halal certificate. The certification process was delayed due to the complexity of the raw material supply chain. The research recommends Mixue to increase transparency, build open communication with the Muslim community, and strengthen internal halal management as a form of commitment to business ethics. This step is important to restore public trust and adjust to local cultural values. This study confirms the importance of integrating business ethics and social responsibility in the strategies of foreign companies in markets with high religious and cultural sensitivity.